MIC food : shaping the right decision-making process for the future - Pendergast, Jennifer M.; Waikar, Sachin (London : Kellogg School of Management, 2022)
This case concerns a family business's efforts to assess and shape collective decision-making among a large sibling leadership group and transition from an informal founder-led operation to a more formalized organization. In late 2021, the family behind MIC Food, a Miami-based processor and distributor of tropical fruits and vegetables, such as plantains, was led by six second-generation siblings, the children of the Honduran-immigrant company founders. The business had come through the onset of the COVID-19 pandemic well, with record expected annual revenue. But as competition and regulation increased, the siblings had to consider whether their informal decision-making-including weekly meetings and regular group texts-should be systematized to ensure strategic and efficient decision-making in the future. Readers will put themselves in the siblings' shoes to consider the best approaches to gaining consensus on strategy and growth goals; sharing power within the sibling group and, potentially, with executives brought in from outside; and creating vision and objectives for bringing the third generation into the enterprise.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Family-owned business enterprises -- Decision making -- Case studies; Decision making -- Case studies